Criticism over Feminism Opinions toward the Regulation of the Abortion Law in Indonesia | النقد على الموافق النسوية تجاه تنظيم قانون الإجهاض في إندونيسيا - Aida Humaira (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2017)
The issue of abortion in Indonesia has a strict and clear legal regulation. Formally, abortion is not justified in Indonesia, so anyone who has been proven to have an abortion will be treated with a criminal penalty in exchange for their actions which violate the law. The decision on the legality of abortion in Indonesia is only to protect morality and to try to evaluate the basic values of life. Therefore, how can a nation be considered civilized if immoral acts – such as abortion – are still scattered in different places. In fact, abortion and its law will only lead to an increase in the number of perpetrators, even will be done openly, and consequently anyone who wants to do an abortion will not hesitate because the law provides a guarantee.